Quad Tree-based Level-of-details Representation of Digital Globe (Short Communication) - Porwal, Sudhir (Defence Science Journal, 2013)
Three-dimensional visualization of the geographic data using a digital globe model has been an integral part of a modern GIS system. The visualization of the digital globe model presents many challenges not found in traditional terrain visualization system. The representation of the digital earth (globe) model is important to efficiently render the geographical data without any distortion either at equator or Polar Regions. This paper presents a uniform scheme for efficient quad tree based level-of-details (LOD) representation of the digital globe to minimize the distortion at Polar Regions and meets the requirement of fast frame rate rendering. Defence Science Journal, 2013, 63(1), pp.89-92, DOI:http://dx.doi.org/10.14429/dsj.63.3768